Revision of the Empis (Enoplempis) mira species group (Diptera: Empididae) - Sinclair, Bradley J.; Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2021)
The Empis (Enoplempis) mira species group is revised and includes the type species of Enoplempis and four new species (E. macdonaldi sp. nov., E. submira sp. nov., E. williamturneri sp. nov., E. winkleri sp. nov.). A lectotype is designated for Enoplempis mira Bigot. The species group is defined by the yellow body colour, directionally asymmetrical male hindlegs and geniculate hindlegs in both males and females. The group has not been found outside of western North America and is known from California, Oregon, Idaho and Washington.